The Economic Impact of Carbapenem Resistant-Non Lactose Fermenter and Enterobacteriaceae Infections on Hospital Costs in Dr. Soetomo General Academic Hospital Surabaya, Indonesia - Yasmeen Lashari; Maftuchah Rochmanti; Abdul Khairul Rizki Purba; Hari Basuki Notobroto; Rosantia Sarassari; Kuntaman Kuntaman (MDPI AG, 2022)
Background: Carbapenem resistant-non lactose fermenter (CR-NLF) and Carbapenem resistant-Enterobacteriaceae (CR-E) bacterial infections are likely to be a global threat to people's health. However, studies on the economic impacts according to the hospital setting are very scarce. The study aimed to explore the impact of CR-NLF (Acinetobacter baumannii = CRAB) & Pseudomonas aeruginosa = CRPA) and CR-E (Escherichia coli = CREC) & Klebsiella pneumoniae = CRKP) infections on hospital costs from a payer perspective among patients admitted to Dr.Soetomo Hospital, Surabaya, Indonesia. Methods: In the retrospective case-control study, medical records of all included patients hospitalized during 2018-2021 were reviewed for CRAB, CRPA, CREC, CRKP, and carbapenem sensitive (CSAB, CSPA, CSEC, CSKP) were collected. We retrieved the data of age, gender, clinical specimen, dates of admission, and discharge status. The outcomes of interest were hospital length of stay and hospitalization cost. Results: The cost for CR-NLFs infections was higher than carbapenem sensitive, $3026.24 versus $1299.28 (p < 0.05). There was no significant difference between CR-E against carbapenem sensitive. It showed that the highest impact of the cost was CRAB, followed by CRPA, CRKP, and CREC. The bed, antibiotics, pharmacy, and diagnostic costs of CR-NLFIs were significantly higher than CR-E. Conclusion: This study showed that the hospital cost and expenditure of CR-NLFs per patient were higher than CS. The hospital cost per patient for CR-NLF was higher than CR-E.